ISPC Assessment of Flagship 2: Small-Scale Fisheries - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2017)
ISPC Assessment of Flagship 2 (Small-Scale Fisheries) of the CGIAR Research Program on Fish Agri-Food Systems (2017-2022). FP2 FISH aims to sustain and increase the contribution of Small-Scale Fisheries to poverty reduction and food and nutrition security.